Determining satisfaction of social media use among Iraqi audiences toward religious issues - Hussein Saadi Mohammed Ali,; Megat Al-Imran Yasin,; Syed Agil Syekh Alsagoff, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This research aims to determine the level of satisfaction on social media use among Iraqi audiences in fulfilling their need for information on religious issues and Islamic topics. This research highlights the role of new media in spreading religious awareness among the public as electronic media is no longer used to just monitor an event and communicate information; rather, it has the power to influence the behaviour of users - hence becoming the pressure and control factors as well triggering event thus creating motivation to prepare an individual in regards of their faith at the same time. A questionnaire was distributed to Iraqi audiences and the results demonstrate the importance of social networking platforms towards shaping attitudes and perceptions towards the practice of Islam and how it has become an integral part of individual behaviour as well as their daily lifestyles. This research was guided by the theory of Uses and Gratification (U&G), where representation of knowledge and information-seeking behaviours influence public opinions on religious issues through the use of social networking sites. Further to this, the results of this search indicate that the motives of social media platform use by the Iraqi public are mostly cognitive and enhanced their knowledge of religious issues.